Contribuições ao debate sobre autonomia e liberdade de expressão em tempos de convergência e Educação Aberta - Andrea Cristina Versuti; Marco Aurélio R. da Cunha e Cruz; Carlos Costa (Araucaria)
This paper aims to present a contribution of new forms of communication, expression, interaction, collaboration and integration for the potential construction of knowledge, through open educational resources, in the current culture of mobility and convergence. To achieve this end, this text focus on the importance of re-reading of freedom of expression as a democratic enlargement vehicle and plural of other freedoms; the impact of the Internet and other emerging thinking in the development of the autonomy of the subject; the characterization of the current scenario of convergence culture with its possibilities for Open Education that stimulates collective intelligence and participatory culture.